PARIWISATA DAN PERUBAHAN SOSIAL DI KAMPUNG NAGA DESA NEGLASARI KECAMATAN SALAWU KABUPATEN TASIKMALAYA PROVINSI JAWA BARAT - HAMDANI, HAMDAN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Since the first Kampung Naga society known as a society which uphold indigenous ancestral traditions, but at this time the progress which occured in various aspects of social life and tourism activities that comes into Kampung Naga, has brought much new value to Kampung Naga. Therefore, whether great or small, fast or slow, changes in social, economic and physical environment in Kampung Naga is unavoidable. Here be interesting in this research to examine phenomena of tourism with all the changes as a tourism counsequent that occur in Kampung Naga. This thesis aims to understanding how tourism activity can change the social, economic and physical environment in Kampung Naga. In this study the author uses qualitative research with ethnographic methods. In general, ethnographic research is described as a form of social research that emphasizes the exploration of the social phenomenon in its original setting, the data used is not structured, the research is micro, data analysis includes the interpretation of the meaning and function of human action, and the results of the analysis is verbal description and some explanation. The result of this research shows the society of Kampung Naga which unique and different with their social life, gradually starting to change indeed in their economic life and physical environment. The high intensity of tourism activities that take place in that place at the end led to the changes in society and the physical environment in Kampung Naga itself.